100-years’ story of success: photoelasticity — LSR–MICE – MSUCE - Vadim N. Savostyanov (Moscow State University of Civil Engineering (MGSU), 2021)
Introduction. The 100-years’ history of MICE – MSUCE is also a history of establishment and flourishing of one of the world’s most powerful experimental school of development and application of the photoelasticity method in the investigation of the stress state of civil and special structures. Reliable forecast of the stress state of buildings and structures under static, thermal and dynamic impacts is an indispensable prerequisite of safe operation provision of civil structures during the construction and the operation. The photoelasticity method, allows, along with the analytical methods of the mechanical science, for continual study of the stress state of the object under test, being an experimental method efficiently used both in “standalone” mode and in conjunction with numerical methods. The goal and the objectives hereof: a retrospective development review of the photoelasticity method, in particular, of the contribution of LSR of MICE, and the assessment of the contemporary state of the method in terms of its actuality, novelty and practical significance of mechanical problem solutions, of stress-strain state studies of structures and buildings.